Characterization of the metabolism of eupalinolide A and B by carboxylesterase and cytochrome P450 in human liver microsomes - Li, Yingzi; Liu, Xiaoyan; Li, Ludi; Zhang, Tao; Gao, Yadong; Zeng, Kewu; Wang, Qi (Frontiers in Pharmacology, 2023)
Eupalinolide A (EA; Z-configuration) and eupalinolide B (EB; E-configuration) are bioactive cis-trans isomers isolated from Eupatorii Lindleyani Herba that exert anti-inflammatory and antitumor effects. Although one pharmacokinetic study found that the metabolic parameters of the isomers were different in rats, metabolic processes relevant to EA and EB remain largely unknown. Our preliminary findings revealed that EA and EB are rapidly hydrolyzed by carboxylesterase. Here, we investigated the metabolic stability and enzyme kinetics of carboxylesterase-mediated hydrolysis and cytochrome P450 (CYP)-mediated oxidation of EA and EB in human liver microsomes (HLMs). We also explored differences in the hydrolytic stability of EA and EB in HLMs and rat liver microsomes (RLMs). Moreover, CYP reaction phenotyping of the isomers was performed via in silico methods (i.e., using a quantitative structure-activity relationship model and molecular docking) and confirmed using human recombinant enzymes. The total normalized rate approach was considered to assess the relative contributions of five major CYPs to EA and EB metabolism. We found that EA and EB were eliminated rapidly, mainly by carboxylesterase-mediated hydrolysis, as compared with CYP-mediated oxidation. An inter-species difference was observed as well, with faster rates of EA and EB hydrolysis in RLMs. Furthermore, our findings confirmed EA and EB were metabolized by multiple CYPs, among which CYP3A4 played a particularly important role.